Menumbuhkan Budaya Gemar Membaca Didalam Mewujudkan Prestasi Siswa Sekolah Dasar - Geby Claudia Purba; Berlianti Berlianti (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
Teachers as educators should set a good example for students in a culture of fond of reading. Apart from teachers, parents also have a very important role in cultivating a culture of liking to read, because the most time students have is the time when they are with their parents at home. The environment also influences the growth of a reading culture. We can see this when students are not at school, so it cannot be denied that students spend more time watching TV, playing gadgets and students use it to chat with various applications. It is necessary to instill in students a culture of liking to read and awareness of the benefits of reading with this in mind that students realize that reading can improve student achievement. The problem solving process is carried out in the PKL 1 mini project activities using the casework method, through the general intervention stage which consists of: Engagement, Intake, Contract, Assessment, Planning, Intervention, Evaluation and Termination. What is the focus of the client's problem solving process is the lack of a culture of fond of reading books. This is because the client lacks the desire to read books. The objectives of the program have been achieved, as evidenced by the client always repeating at home the subjects taught at his school. The client always answers the questions given by the teacher correctly.